Spectroscopic and DFT study of a glutamic acid Nd(III) complex - Takahashi, Issei; Nakane, Daisuke; Akitsu, Takashiro; Sinha, Chittaranjan (European Journal of Chemistry, 2025)
Due to the large number of electrons occupying 4f orbitals, the computational chemistry of lanthanide complexes is not as easy as that of d-block ones. As a result, even though lanthanide molecules have attracted attention in various fields in recent years, there has been little research on their spectrochemical properties or computational science in detail. In this study, we experimentally measured electronic, circular dichroism (CD), fluorescence, and infrared (IR) spectra as well as the direct current (DC) magnetic susceptibility curves (magnetization (M) versus magnetic field (H) curves (MH) and magnetization (M) versus temperature (T) curves (MT)) of a mononuclear Nd(III) complex with a glutamic acid ligand and to test the density functional theory (DFT) calculation conditions that can be performed from the structure optimization. Bands of C=O and N-H were observed in the IR spectrum, and paramagnetism was confirmed by measurements. The fluorescence intensity of the DMSO solution at 300 K was very weak. Ultraviolet-visible (UV-vis) and CD spectra showed a strong intraligand transition at 200-250 nm and relatively strong sharp f-f transitions at 581, 742, and 801 nm (like the solvated Nd(III) ion). Thus, herein we synthesized lanthanide Nd(III) complexes coordinated with amino acids and conducted structure estimation research by comparing experimental measurement results such as electron microscopy, spectroscopy, and magnetism with DFT calculations (optimized structure). Lanthanide complexes are difficult to study because their coordination numbers are large, their solution structures are unclear, and their large number of electrons makes computational chemistry difficult. In general, metals have large ionic radii, and thus can potentially have high coordination numbers. Metal ions of hard Lewis acids prefer hard-base ligands (especially oxygen atoms in water and amino acids). Therefore, it is interesting to try to easily understand the structure in solution by comparing spectroscopic experiments with computational chemistry.